BRCA mutation in breast cancer patients: Prognostic impact and implications on clinical management. Issue 6 (31st July 2018) - Loi, Mauro; Desideri, Isacco; Olmetto, Emanuela; Francolini, Giulio; Greto, Daniela; Bonomo, Pierluigi; Simontacchi, Gabriele; Di Brina, Lucia; Meattini, Icro; Livi, Lorenzo
Abstract: BRCA1/2 mutations are involved in breast cancer (BC) susceptibility but their influence on outcome is unclear. We reviewed BC patients tested for BRCA to determine biological features and influence on outcome. BRCA‐1 was correlated to younger age ( P = 0.035), nodal involvement ( P = 0.030), higher tumor grade ( P = 0.0022) and Ki‐67 ( P = 0.014), ER/PgR negative status ( P = 0.00042 and 0.0091, respectively), and use of adjuvant chemotherapy ( P = 0.000038); BRCA was neither predictive for chemotherapy administration nor resulted in impaired outcome or occurrence of secondary BC. BRCA status did not influence outcome despite higher biological aggressiveness and younger age at presentation.